Sosialisasi Dampak Penggunaan Gadget Terhadap Anak Di Dusun II Desa Pematang Setrak Kecamatan Teluk Mengkudu Kabupaten Serdang Bedagai - Sapriadi; Muhammad Crystandy; Khairul Umam Syaliman (JITER-PM (Jurnal Inovasi Terapan - Pengabdian Masyarakat), 2023)
The development of the times in this era the use of gadgets in children is considered a natural thing. For some parents, gadgets are an easy solution to calm fussy children. This triggers the tendency for children to keep asking their parents for gadgets. On average, they have early childhood problems with excessive gadget use. The problems found and the solutions offered are for parents who often complain about the existence of gadgets that interfere with their children's activities, which has an impact on the development of the behavior and mindset of children who are easily influenced by gadgets and are difficult to communicate with. For this reason, the purpose of this activity is to provide knowledge to parents about the impact of using gadgets in early childhood. This activity is expected to be able to provide understanding to parents how important it is to accompany mothers (parents) when children use gadgets, understand how important time discipline is in using gadgets and understand how important it is to be smart in using gadgets. The method used for the implementation of this outreach activity is to use a participatory approach. With this participatory method, participants will be actively involved in every stage and socialization activities, which will be carried out through counseling, discussions. The result of implementing this socialization is that parents in Hamlet II of Pematang Setrak Village gain understanding and knowledge about the importance of protection in accompanying children to play gadgets and the importance of communicating with children, so as to prevent anti-social behavior from an early age in children.